Europol and the contrast of the illegal weapons trade (arms trafficking) via computer (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
This essay underlines the growing contribution of Europol to the efforts of Member States and the EU in fighting transnational organized crime and terrorism. The author stresses that Europol’s support for and cooperation with national law enforcement agencies is of paramount importance to counter more effectively illicit firearms trafficking, including its most evolutionary forms through the Darknet marketplaces.Keywords: European Union, Europol, Law Enforcement Cooperation, cybercrime, darknet